Health education in primary care: a look under the perspective of users of the healthcare system - Fittipaldi, Ana Lúcia de Magalhães; O’Dwyer, Gisele; Henriques, Patrícia (Saúde e Sociedade, 2024)
This article aims to analyze the action of health education in primary healthcare, under the perspective of users of the healthcare system, in view of Bourdieu’s social action theory. It is qualitative research held in two Primary Healthcare Centers in the municipality of Rio de Janeiro. Participant observation and semi-structured interviews were used as research techniques. A total of twelve interviews were conducted, with three analytical categories: autonomy and vulnerability: the agent’s social trajectory; extended health care: meanings and tensions experienced from symbolic capitals; and bonding, trust and affection: the social support network. The analysis of the interviews featured Bardin’s content analysis as theoretical framework in its thematic aspect. The collective actions opened space for dialog and appreciation of everyone’s ideas, and the coordination of the concepts of Bourdieu’s sociology of action with health education contributed to the understanding of the user’s perspective about these social practices. Finally, effective and transforming actions by using dialog and interaction with the dynamics of the lives of the common people are proposed.